2018
DOI: 10.1111/1750-3841.14293
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Interactions Occurring During the Encapsulation of Sesamol within Casein Micelles Reformed from Sodium Caseinate Solutions

Abstract: The development of a nanodelivery system for different bioactives will allow the enrichment of foods and drinks to develop new functional products that will satisfy consumers' demands. Additionally, the study of interactions between these molecules will allow us to understand how sesamol is being incorporated within the reformed micelles and how this process can even be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…7,17,18 NaCas is an attractive carrier that has been used for the delivery of poorly water soluble natural ingredients such as folic acid, quercetin, naringenin, curcumin, vitamin D, sesamol, curcumin, quercetin, and eugenol. 13,[19][20][21][22][23][24][25][26] Recently, we successfully obtained sodium caseinatemaltodextrin nanocomplex nanocarriers loaded with propolis extract (PE). 27 In this context, the major purposes of this work were to design…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,17,18 NaCas is an attractive carrier that has been used for the delivery of poorly water soluble natural ingredients such as folic acid, quercetin, naringenin, curcumin, vitamin D, sesamol, curcumin, quercetin, and eugenol. 13,[19][20][21][22][23][24][25][26] Recently, we successfully obtained sodium caseinatemaltodextrin nanocomplex nanocarriers loaded with propolis extract (PE). 27 In this context, the major purposes of this work were to design…”
Section: Introductionmentioning
confidence: 99%
“…As an aqueous‐soluble biopolymer with randomly coiled structure and unique self‐binding character, NaCas hosts both hydrophobic and hydrophilic molecules, making it a valid carrier to encapsulate an extensive variety of bioactive agents 7,17,18 . NaCas is an attractive carrier that has been used for the delivery of poorly water soluble natural ingredients such as folic acid, quercetin, naringenin, curcumin, vitamin D, sesamol, curcumin, quercetin, and eugenol 13,19–26 . Recently, we successfully obtained sodium caseinate‐maltodextrin nanocomplex nanocarriers loaded with propolis extract (PE) 27 .…”
Section: Introductionmentioning
confidence: 99%
“…26 Santos Basurto founded encapsulated sesamol within casein micelles re-formed from sodium caseinate solutions; as the concentration of caseinate solutions was increased from 2% to 5%, the encapsulation efficiency of sesamol increased from 27.7% to 34.9%. 27 SC, as stabilizer and thickener, has been permitted in a widespread range of applications in the food industry. 28,29 In addition, SC has been used to improve the stability of several pigments.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang Lihua used SA and SC as wall materials to prepared the Lactobacillus plantarum CICC 20022 microcapsules; the results indicated that the encapsulation efficiency of SA‐SC microcapsule and SA microcapsule were 46.08% and 42.72%, respectively 26 . Santos Basurto founded encapsulated sesamol within casein micelles re‐formed from sodium caseinate solutions; as the concentration of caseinate solutions was increased from 2% to 5%, the encapsulation efficiency of sesamol increased from 27.7% to 34.9% 27 . SC, as stabilizer and thickener, has been permitted in a widespread range of applications in the food industry 28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Since 2014, casein has been proposed as a raw material for the formation of micro and nano capsules because of its high affinity for hydrophobic substances and is Generally Recognized as Safe (GRAS) substance [4] .Casein has been used to encapsulate different substances in the food industry. Examples of lipophilic organic substances include: omega-3 fatty acids, [5] β-carotene, [1,6,7] fish oil, [8] curcumin, [9][10][11][12] vitamin A, vitamin D, [13,14] , vanillin, [15] eugenol, [16] triclosan, [17] thymol, [18] celecoxib, [19] emodin, [20] sunflower oil, [21] resveratrol, [22,23] hydroxycamptothecin, [24] quercetin, [9] blueberry anthocyanins, [2] naringenin, [25] isoflavone, [25] rutin [4] and linoleic acid [26] ; and hydrophilic organic substances such as: vitamin C [27] and phenolic compounds . [28] On the other hand, nanoparticles of inorganic substances have been encapsulated using caseins, such as iron oxide, [29] calcium carbonate, [30] zinc oxide, [31] silver, gold and copper(II) oxide .…”
Section: Introductionmentioning
confidence: 99%